Pemilu dalam Perspektif Hadis Riwayat Al-Bukhari Mengenai Larangan Memilih Pemimpin yang Tidak Kompeten - Rayhan Nadindra Alfatih; Tajul Arifin (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the Islamic perspective on the process of electing leaders, focusing on the hadith narrated by Al-Bukhari that warns of the dangers of entrusting authority to those who are not qualified. Using a descriptive-analytical method with a normative juridical approach, this research analyzes primary sources such as the hadiths in Sahih Al-Bukhari and relevant statutory regulations, supported by secondary sources from related scholarly literature. The findings reveal that leadership in Islam is a great trust (amanah) that demands strict fulfillment of Shari'ah criteria, including justice, trustworthiness, knowledge, and honesty. Entrusting leadership to incompetent individuals may lead to widespread social and political collapse, as indicated by the Prophet Muhammad (peace be upon him) in his hadith. Furthermore, the community’s negligence in electing suitable leaders is considered a collective sin that significantly affects societal stability. Therefore, Muslims must exercise greater vigilance, critical thinking, and responsibility in choosing their leaders to maintain social order in line with the principles of shura and Islamic values.